2022
DOI: 10.1002/ags3.12603
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of sarcopenic dysphagia for patients with esophageal cancer undergoing esophagectomy: A review

Abstract: Recently, minimally invasive esophagectomy and perioperative management have been adopted with the aim of reducing surgical complications after esophagectomy. 1 However, pulmonary complications after esophagectomy sometimes lead to fatalities 2 ; therefore, prevention is an important consideration in perioperative management.One of the most important reasons for postoperative pneumonia is dysphagia. Old age, malnutrition, sarcopenia, multiple primary cancers, vocal code paralysis, and so on have been implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Hence, omitting the non-fluorescent LN resection should be indicated only to avoid postoperative recurrent nerve paralysis in exchange for the possibility of remaining metastatic LNs. Furthermore, several recent studies have suggested the association of preoperative sarcopenia with the development of dysphagia after esophagectomy [ 38 , 39 ]. In patients with advanced cancer with severe sarcopenia, preventing postoperative malnutrition due to dysphagia may have a higher priority than performing the complete LN dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, omitting the non-fluorescent LN resection should be indicated only to avoid postoperative recurrent nerve paralysis in exchange for the possibility of remaining metastatic LNs. Furthermore, several recent studies have suggested the association of preoperative sarcopenia with the development of dysphagia after esophagectomy [ 38 , 39 ]. In patients with advanced cancer with severe sarcopenia, preventing postoperative malnutrition due to dysphagia may have a higher priority than performing the complete LN dissection.…”
Section: Discussionmentioning
confidence: 99%
“…However, no consistent data regarding the degree or severity are available, limiting their value for individual risk prediction. 7,8 In this context, medical imaging may be a promising tool for opportunistic risk assessment in routine postoperative staging computed tomography (CT) on the basis of changes in the anatomy that may be more sensitive and accurate than traditional risk factors. 9 In particular, CT-derived changes in body composition (BC; ie, subcutaneous adipose tissue [SAT], visceral adipose tissue [VAT], and skeletal muscle [SM]) from routine staging may serve as a robust and low-cost prognostic tool in patients with GEAC without the need for additional testing.…”
Section: Introductionmentioning
confidence: 99%
“…10,14 Sarcopenia-and malnutrition-associated dysphagia contribute to respiratory adverse events after surgery. 15 However, the association between these factors and post-ESD pneumonia in patients with superficial esophageal cancer has not been comprehensively studied. Furthermore, swallowing function assessment is complex and requires multidisciplinary partnership and comprehensive examination.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding esophageal cancer, ESD can cause an increase in esophageal pressure and dysphagia 10,14 . Sarcopenia‐ and malnutrition‐associated dysphagia contribute to respiratory adverse events after surgery 15 . However, the association between these factors and post‐ESD pneumonia in patients with superficial esophageal cancer has not been comprehensively studied.…”
Section: Introductionmentioning
confidence: 99%